2021
DOI: 10.3389/fmars.2021.696389
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Constraints and Variability in the Analysis of Bacterial Community Structures in the Sea Surface Microlayer

Abstract: The sea surface microlayer (SML) is a thin surface film located at the interface between oceans and the atmosphere. In this study, three SML samplers—polycarbonate membrane (PC), glass plate (GP), and drum sampler (DS)—were used to collect microbiological DNA samples for molecular analysis. Among the three samplers, DS only took half the time to sample the SML compared to GP while PC were able to sample the thinnest SML depth. Biological matter and distinct bacterial communities in the SML were apparent during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Strains used in this study were isolated from the sea surface microlayer (SML) of coastal Sagami Bay, Japan (35°09′04″N, 139°08′47″E). SML samples were collected by placing 47 mm polycarbonate membrane filters (Whatman, United Kingdom) onto the water surface for 10 s and spread onto 1/10-strength ZoBell agar plates ( 6 8 ). The plates were irradiated with UV-C (254 nm) at 595 μW/cm 2 for 60 s using a handy UV lamp (UVGL-25, Funakoshi, Japan) and incubated at 25°C for 2 weeks under white light condition.…”
Section: Announcementmentioning
confidence: 99%
“…Strains used in this study were isolated from the sea surface microlayer (SML) of coastal Sagami Bay, Japan (35°09′04″N, 139°08′47″E). SML samples were collected by placing 47 mm polycarbonate membrane filters (Whatman, United Kingdom) onto the water surface for 10 s and spread onto 1/10-strength ZoBell agar plates ( 6 8 ). The plates were irradiated with UV-C (254 nm) at 595 μW/cm 2 for 60 s using a handy UV lamp (UVGL-25, Funakoshi, Japan) and incubated at 25°C for 2 weeks under white light condition.…”
Section: Announcementmentioning
confidence: 99%
“…Nevertheless, while some studies found that the bacterioneuston was enriched in specific taxa compared to the ULW (Franklin et al, 2005, Zäncker et al, 2018, others report no significant differences between the two layers (Agogue et al, 2005, Obernosterer et al, 2008. These discrepancies might be the results of spatiotemporal variations, winds, and SSML chemical properties but also be the results of the SSML collection method (Stolle et al, 2010, Cunliffe et al, 2011, Rahlff et al, 2017, Wong et al, 2021.…”
Section: Introductionmentioning
confidence: 98%
“…We choose these two leaching material sources due to the evidence that the potential impact of Antarctic coastal ecosystems on aerosol composition has been overlooked in past studies (Decesari et al, 2020;Rinaldi et al, 2020). The sea-surface microlayer (SML) -a <1 mm layer at the air-sea boundary, and spontaneously emerging surface phenomena, such foams -patches floating on the water surface (Wong et al, 2021;Rahlff et al, 2021) -are found increasing research interest (Wurl et al, 2017;Engel et al, 2017). The main objective of this work is to test whether organic leaching material from ecologically rich coastal ecosystems has an effect on sea spray aerosol production in the sensitive area of the AP.…”
Section: Introductionmentioning
confidence: 99%